2004
DOI: 10.1097/00000542-200407000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Response to Epidural Analgesia in Laboring Patients by Wavelet Transform of Heart Rate and Blood Pressure Variability

Abstract: Indices of parasympathetic and sympathetic activity after neuraxial blockade in laboring patients can be obtained by analysis of both heart rate variability and blood pressure variability. The analysis by wavelet transform can discern changes in autonomic activity when values of blood pressure and heart rate do not vary significantly. Whether this technique could be used to predict and prevent hemodynamic compromise after neuraxial blockade merits further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
27
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 29 publications
4
27
2
3
Order By: Relevance
“…This will allow the opportunity to see whether the changes occurring at skin microcirculation level as detected through the LDF signal could have a significant impact on the VLF region of the HRV signal. Deschamps et al (2004) also observed increase in power of the HF band and decrease in the LF/HF ratio values after the application of local anaesthesia, but in this case there were two problems. Firstly, they have analysed data from labouring patients undergoing epidural anaesthesia as compared to patients included in this study which received brachial plexus block for hand surgery.…”
Section: Discussionmentioning
confidence: 68%
“…This will allow the opportunity to see whether the changes occurring at skin microcirculation level as detected through the LDF signal could have a significant impact on the VLF region of the HRV signal. Deschamps et al (2004) also observed increase in power of the HF band and decrease in the LF/HF ratio values after the application of local anaesthesia, but in this case there were two problems. Firstly, they have analysed data from labouring patients undergoing epidural anaesthesia as compared to patients included in this study which received brachial plexus block for hand surgery.…”
Section: Discussionmentioning
confidence: 68%
“…12 For sympathetic tone, it is analysis of blood pressure variability that has been the most reliable measure. [13][14][15] This signal is obtained from a continuous blood pressure tracing, and the analysis of beat-to-beat variations in blood pressure. Thus in order to "monitor" parasympathetic and sympathetic tone, it is necessary to measure both heart rate and blood pressure variability.…”
mentioning
confidence: 99%
“…This has been done successfully in the past, using post-hoc analysis to show changes in both arms of the autonomic nervous system resulting from labour analgesia, using an epidural technique. 13,14 Most cardioactive and vasoactive medications used in anesthesia have specific effects on heart rate and blood pressure variability and thus, the effect of these agents could be followed quite easily in terms of autonomic tone.…”
mentioning
confidence: 99%
See 2 more Smart Citations